METHOD OF RATIONAL CHOICE OF SOME ELECTROMECHANICAL DEVICES AND THEIR SERIES - Zagirnyak, Mykhaylo; Prus, Vyacheslav; Nikitina, A.V. (Journal of Energy Technology, 2024)
An approach to improvement of interconnections of a summarised geometric dimension and the power parameters of electric machines, transformers and electric devices is determined based on a generalisation of theoretical and experimental research results.